2018
DOI: 10.7589/2017-04-071
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pseudorabies Virus Shedding in Feral Swine (Sus Scrofa) Populations of Florida, Usa

Abstract: :  Feral swine ( Sus scrofa) are a pathogen reservoir for pseudorabies virus (PrV). The virus can be fatal to wildlife and contributes to economic losses in the swine industry worldwide. National surveillance efforts in the US use serology to detect PrV-specific antibodies in feral swine populations, but PrV exposure is not a direct indicator of pathogen transmission among conspecifics or to non-suid wildlife species. We measured antibody production and the presence of PrV DNA in four tissue types from feral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Considering the virological analysis, only one out of 24 pregnant sows shed the virus, as indicated by the PCR positive result on the nasal-genital swab. This data is in accordance with other studies that identified percentages of shedding individuals ranging from 1% to 6% inside of a population with high seroprevalence rates (50%-60%) [7,9]. Interestingly, pooled foetuses collected from the pregnant sows also resulted in positive to virological analysis, indicating the ability of PRV to infect the foetuses during pregnancy in a viraemic status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Considering the virological analysis, only one out of 24 pregnant sows shed the virus, as indicated by the PCR positive result on the nasal-genital swab. This data is in accordance with other studies that identified percentages of shedding individuals ranging from 1% to 6% inside of a population with high seroprevalence rates (50%-60%) [7,9]. Interestingly, pooled foetuses collected from the pregnant sows also resulted in positive to virological analysis, indicating the ability of PRV to infect the foetuses during pregnancy in a viraemic status.…”
Section: Discussionsupporting
confidence: 92%
“…This appears to be in contrast with the previous literature, in which higher seroprevalence rates are generally reported in females. In fact, sows live in "maternal groups" [3,9,39] and therefore have a greater possibility of oronasal transmission of the virus between individuals, compared to males who are solitary and meet their conspecifics only during the mating season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since feral swine home ranges are typically influenced by food availability and unrestricted compared to livestock, movement to a neighboring county would not be unexpected [ 23 ]. Though serological results are not equivalent to shedding rates, evidence of viral shedding has been detected in multiple tissue types suggesting various routes of transmission [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States (U.S.) there are ∼6 million invasive feral swine (Sus scrofa), which are defined as any released or escaped domestic pigs, Eurasian wild boars, or hybrids of the two (1,2). Both the abundance of feral swine and extent of the geographic range have increased rapidly over the past 30 years due to the high reproductive potential of the species, limited predation pressure, abundance of food (both native flora and fauna and agricultural products), and human-mediated introduction into uninvaded habitats (3,4). As range and abundance have increased, so too have the economic and ecological costs of feral swine.…”
Section: Introductionmentioning
confidence: 99%